Kewenangan dan Peranan Notaris dalam Pembuatan Akta Pendirian Perusahaan - Deka Indra Putra Utama; Indratirini Indratirini (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Notaries play a key role in passing legal documents needed to establish a company. This includes the deed of establishment of the company, changes in the articles of association, and changes in other company structures. Deed of establishment of the company is a basic document that established a company. This deed contains information about company names, company goals, addresses, basic capital, management, and other related matters. The notary will pass this deed. This document regulates the rules and internal structures of the company, including the rights and obligations of shareholders, management rights, and other regulations. Nevertheless, there are some authority and role of the notary that must be carried out in making the company's establishment deed. The objectives in this study are to explain the authority and role of the notary in making a deed of establishment of the company. The approach used in this study is a juridical-empirical approach. The results in this study are the authority and role of the notary in making a deed of establishment of companies in Indonesia is very important and regulated by clear legal regulations. This is regulated by Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning Notary Position. Notaries have the authority to compile a deed of establishment of the company. This deed of establishment contains information about the company to be established, including company names, company goals, basic capital, management composition, and other matters relating to company establishment. The notary conducts an inspection to ensure that the company's establishment deed meets the legal requirements in force in Indonesia.